2017
DOI: 10.3389/fnins.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Music Perception in Young Children: Evidence for and Psychometric Features of the M-Factor

Abstract: Given the relationship between language acquisition and music processing, musical perception (MP) skills have been proposed as a tool for early diagnosis of speech and language difficulties; therefore, a psychometric instrument is needed to assess music perception in children under 10 years of age, a crucial period in neurodevelopment. We created a set of 80 musical stimuli encompassing seven domains of music perception to inform perception of tonal, atonal, and modal stimuli, in a random sample of 1006 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
(89 reference statements)
1
9
0
1
Order By: Relevance
“…Despite this overall difference, scores did not increase consistently between age groups, especially for the c-MDT. This is similar to a recent large study which found that music perception ability did not increase as a function of age in Brazilian children (Barros et al, 2017 ). Taken together, this suggests a need to consider non-linear growth trajectories in childhood, such as the monotonic function which has been used to describe the development of musical expertise in adults (Ericsson et al, 1993 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite this overall difference, scores did not increase consistently between age groups, especially for the c-MDT. This is similar to a recent large study which found that music perception ability did not increase as a function of age in Brazilian children (Barros et al, 2017 ). Taken together, this suggests a need to consider non-linear growth trajectories in childhood, such as the monotonic function which has been used to describe the development of musical expertise in adults (Ericsson et al, 1993 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although scores are reported for children with up to 2 years of musical training, the test was designed to identify amusia (an auditory-processing deficit), and as such may not be sensitive enough to detect differences in ability between children with and without training, or changes with age. Most recently, researchers developed a battery of tests of music perception, standardized on over 1,000 Brazilian schoolchildren aged 7–13 (Barros et al, 2017 ). Test scores showed no correlations with age, indicating that the task may not be useful in a developmental context.…”
Section: Introductionmentioning
confidence: 99%
“…Current conceptions of musicality define it as an innate, natural, and spontaneous development of widely shared traits, constrained by our cognitive abilities and biology, that underlie the capacity for music (27). While being "musical" no doubt encompasses more than simple hearing or perceptual abilities (e.g., instrumental production creativity), for this investigation we focus on the receptive aspects of musicality (i.e., auditory perceptual skills), following the long tradition of assessing formal music abilities through strictly perceptual measures (28)(29)(30)(31)(32). Among the normal…”
mentioning
confidence: 99%
“…This study's sample came from a wider project designed to assess and validate a battery of music perception (MP) skills among children and young people (Barros et al, 2017). Because the battery consists of 80 items evaluating seven compositional features (contour, timbre, meter, pitch, scale, duration, and loudness), in order to adequately estimate the parameters of the music perception items we considered at least 10 participants per observed indicator variable (i.e., the 80 items) as a rule of thumb for an adequate lower-bound sample size calculation (Nunnally, 1967), resulting in at least 800 children.…”
Section: Sample Size Calculationmentioning
confidence: 99%